Inspector hare and the locked room - Hills, Peter Bennett (Nelson Australia South Melbourne, Vic., 1994)
Inspector Hare and the Locked Room by Peter Bennett Hills is a gripping mystery novel featuring the astute detective Inspector Hare, who is tasked with solving a baffling crime that takes place in a seemingly impenetrable locked room. As he delves into the investigation, Inspector Hare navigates a web of clues, suspects, and unexpected twists, all while using his sharp analytical skills to unravel the mystery. The story is filled with tension and intrigue, as Hare races against time to uncover the truth and bring the culprit to justice. With its clever plotting and engaging characters, the novel keeps readers on the edge of their seats.